Aplikasi Data Usulan Bantuan Sosial Menggunakan PHP pada Dinas Kesejahteraan Sosial Kabupaten Nabire - Deka Mangedong; Ester Ayuk Pusvita; Penison Wenda (Jurnal Teknologi dan Informatika, 2023)
In the process of providing social assistance to the community, of course, it cannot be separated from the process of inputting proposed data. At the Nabire Regency Social Welfare Office, the process of inputting proposed social assistance data uses Microsoft Office Excel, the data input process using Microsoft Office Excel is considered to be inefficient because the data that has been input can be lost, so the admin often inputs data repeatedly. an application in the process of inputting data. Data input using this application will be stored in the PhpMyAdmin database. In making this application using a system design use case diagrams that explain the duties and functions of each actor. The tools used in making this application are Visual Studio Code, PhpMyAdmin, Xampp. This social assistance proposal data application can simplify the inputting process and the data can be printed in the form of a hard copy file.